1998
DOI: 10.1007/bf03038982
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy after radical hysterectomy of the cervical cancer

Abstract: These results suggest that patients with pathologic T1b-T2b cervix cancer with pelvic lymph node metastases are at high risk of recurrence or metastases after radical hysterectomy with pelvic lymphadenectomy and postoperative irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 18 publications
(18 reference statements)
3
23
0
7
Order By: Relevance
“…However, the observed disparity is more likely a function of the observed heterogeneity among study methods (eg, assessment methods and length of followup) than it is of the particular characteristics of the solid tumors reviewed. Increased lymphedema risk was observed for patients undergoing pelvic dissections (22%), 18,23,26,30,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] as well as for those undergoing radiation therapy (31%). 17,24,25,33,36-38,40,42,43,45,46,48,50-54 The high incidence of lymphedema observed for gynecological malignancies (20%) is not surprising given that approximately 70% of the patients in these studies were reported to have undergone pelvic lymph node dissections and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed disparity is more likely a function of the observed heterogeneity among study methods (eg, assessment methods and length of followup) than it is of the particular characteristics of the solid tumors reviewed. Increased lymphedema risk was observed for patients undergoing pelvic dissections (22%), 18,23,26,30,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] as well as for those undergoing radiation therapy (31%). 17,24,25,33,36-38,40,42,43,45,46,48,50-54 The high incidence of lymphedema observed for gynecological malignancies (20%) is not surprising given that approximately 70% of the patients in these studies were reported to have undergone pelvic lymph node dissections and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a previous report, the rate of lymphedema complication in a group of patients who underwent pelvic and para-aortic lymphadenectomy for gynecologic malignancies was found to be 24%. 11 The same researchers suggested that if the surgical approach could be modified, the severity of lymphedema might be reduced.…”
Section: Discussionmentioning
confidence: 95%
“…Seit Einführung der Hochvolttherapie wird in retrospektiven Analysen eine kumulative Inzidenz der Osteoradionekrosen von 0-3% bis zu einer aktuarischen Inzidenz von 11% nach 5 Jahren berichtet [2,3,6,11,15]. In einer systematischen Untersuchung mit Knochenszintigrammen haben Abe et al [1] bei Frauen, die mit durchschnittlich 46 Gy mit 10-MeVPhotonen behandelt worden waren, eine kumulative Inzidenz von Osteoradionekrosen von 34%, die in 22% der Fälle asymptomatisch waren, gefunden.…”
Section: Diskussionunclassified
“…Etwaige Mehranreicherungen wurden nach ihrer Lokalisation beschrieben und die Speicherungsintensität im Vergleich zu Femur und Lendenwirbelsäule als Referenzknochen als gering, mäßig oder stark gewertet. Die im CT sichtbaren knöchernen Veränderungen wurden nach den Kriterien der RTOG klassifiziert: G3 = dichte Sklerose, G4 = Nekrose/Spontanfraktur [6]. Als Osteoradionekrose werden in der CT nachweisbare Frakturen mit und ohne Sklerose oder Kallusbildung, immer aber ohne begleitende weichteildichte Raumforderung, definiert (Abbildung 1).…”
Section: Introductionunclassified